Longer immediate recovery time after anesthesia increases risk of respiratory complications after laparotomy for bariatric surgery: a randomized clinical trial and a cohort study - Sudré, Eliana C. M.; de Batista, Priscila R.; Castiglia, Yara M. M. [UNESP] (Springer, 2015)
We compared the effects of two anesthesia protocols in both immediate recovery time (IRT) and postoperative respiratory complications (PRCs) after laparotomy for bariatric surgery, and we determined the association between the longer IRT and the increase of PRC incidence. We conducted the study in two stages: (i) in a randomized controlled trial (RCT), patients received either intervention (sevoflurane-remifentanil-rocuronium-ropivacaine) or control protocol (isoflurane-sufentanil-atracurium-levobupivacaine). All patients received general anesthesia plus continuous epidural anesthesia and analgesia. Treatment was masked for all, except the provider anesthesiologist. We defined IRT as time since anesthetics discontinuation until tracheal extubation. Primary outcomes were IRT and PRCs incidence within 15 days after surgery. We also analyzed post-anesthesia care unit (PACU) and hospital length of stays; (ii) after the end of the RCT, we used the available data in an extension cohort study to investigate IRT > 20 min as exposure factor for PRCs. Control protocol (n = 152) resulted in longer IRT (30.4 ± 7.9 vs 18.2 ± 9.6 min; p < 0.0001), higher incidence of PRCs (6.58 vs 2.5 %; p = 0.048), and longer PACU and hospital stays than intervention protocol (n = 200); PRC relative risk (RR) = 2.6. Patients with IRT > 20 min (n = 190) presented higher incidence of PRCs (7.37 vs 0.62 %; p < 0.0001); RR = 12.06. Intervention protocol, with short-acting anesthetics, was more beneficial and safe compared to control protocol, with long-acting drugs, regarding the reduction of IRT, PRCs, and PACU and hospital stays for laparotomy in bariatric patients. We identified a 4.5-fold increase in the relative risk of PRCs when morbid obese patients are exposed to an IRT > 20 min.
Keywords: Anesthesia; Bariatric surgery; Obesity; Postoperative complications